Analisis Persepsi Pasien Terhadap Kualitas Pelayanan Rawat Jalan Di RS MISI LEBAK - Sarma Eko Sinaga (Politeknik Kementerian Kesehatan Banjarmasin, 2018)
The purpose of this research is to analyze the perception of the patient on the quality of outpatient service of Lebak Mission Hospital after getting service reliability, responsiveness, assurance, empathy, tangibles. This research was conducted in Lebak Hospital with 110 respondents after receiving outpatient service. The research method is surveyed with the cross sectional approach. Data collection was done by using questionnaires, while data analysis in this research using multivariate analysis Multiple Logistic Regression Prediction Model. Result of statistic test obtained got the odds ratio (OR) variable empathy equal to 5,460 which mean perception of patient after get empathy, service will have better satisfaction equal to 5,5x bigger than patient which do not get empathy service. Variables that are very dominant influence on patient perception is variable empathy. And the related variables significantly to the perception of the patient is empathy and tangible variables.